Zakat and Tax Relations in Muslim Southeast Asian Countries (Comparative Study of Zakat and Tax Arrangements in Indonesia, Malaysia and Brunei Darussalam) - Islamy, Athoillah; Aninnas, Afina (Institut Agama Islam Negeri Kendari, 2020)
This study compares Zakat and tax relations in three countries in the Southeast Asian region, where most of the population is Muslim (Indonesia, Malaysia, and Brunei Darussalam). This type of research is normative, empirical legal analysis with a comparative approach. The results showed relational and functional distinctions in Zakat and tax positions in Indonesia, Malaysia, and Brunei Darussalam. In Indonesia, paying Zakat can reduce taxable income. Meanwhile, Malaysia uses Zakat as a deduction for individual taxes, even up to 100%. Meanwhile, in Brunei Darussalam, the Zakat and tax relationship are not interrelated.